A framework for assessing e-health preparedness. (14th March 2005) - Wickramasinghe, Nilmini S.; Fadlalla, Adam M.A.; Geisler, Elie; Schaffer, Jonathan L.
Whilst healthcare is the biggest service industry on the globe, it has yet to realise the full potential of the e-business revolution in the form of e-health. This is due to many reasons including the fact that the healthcare industry is faced with many complex challenges in trying to deliver cost-effective, high-value, accessible healthcare and has traditionally been slow to embrace new business techniques and technologies. Given that e-health, to a great extent, is a macro level concern that has far reaching micro level implications, this paper firstly develops a framework to assess a country's preparedness with respect to embracing e-health (the application of e-commerce to healthcare) and from this an e-health preparedness grid to facilitate the assessment of any e-health initiative. Taken together, the integrative framework and preparedness grid provide useful and necessary tools to enable successful e-health initiatives to ensue by helping country and/or an organisation within a country to identify and thus address areas that require further attention in order for it to undertake a successful e-health initiative.